Reprogramming alternative macrophage polarization by GATM-mediated endogenous creatine synthesis: A potential target for HDM-induced asthma treatment - Yu, Li; Wang, Lingwei; Hu, Guang; Ren, Laibin; Qiu, Chen; Li, Shun; Zhou, Xiaohui; Chen, Shanze; Chen, Rongchang (Frontiers in Immunology, 2022)
Cellular energy metabolism plays a crucial role in the regulation of macrophage polarization and the execution of immune functions. A recent study showed that Slc6a8-mediated creatine uptake from exogenous supplementation modulate macrophage polarization, yet little is known about the role of creatine de novo biosynthesis pathway in macrophage polarization. Here, we observed that glycine amidinotransferase (GATM), the rate-limiting enzyme for creatine synthesis, is upregulated in alternative (M2) polarized macrophage which dependent on the transcriptional factor STAT6, whereas its expression is suppressed in classic activated (M1) macrophage. Next, we revealed that the creatine exogenous supplementation enhanced IL-4 induced M2 polarization, which confirmed the results from a recent study. Furthermore, we revealed that genetic ablation of GATM did not affect M1 marker genes expression (Nos2, IL1b, IL12b) and the production of nitric oxide in both peritoneal macrophage (PM) and bone marrow-derived macrophages (BMDM). By contrast, the expression levels of M2 markers (Arg1, Mrc1, Ccl17 and Retnla) were reduced by GATM deletion. Moreover, we found that deletion of GATM in resident alveolar macrophages significantly blocked M2 polarization but with no obvious effect on cell number of knockout mice. Lastly, an upregulation of GATM was found in HDM induced asthmatic lung tissue and bronchoalveolar lavage fluid macrophage. Our present study uncovers a previously uncharacterized role for creatine de novo biosynthesis enzyme GATM in M2 macrophage polarization, which may potentially involve in pathogenesis of related inflammatory diseases such as an T helper 2 (Th2)-associated allergic asthma.